The impact of asymptomatic helminth co-infection in patients with newly diagnosed tuberculosis in north-west Ethiopia. - Ebba Abate (PLoS ONE, 2012)
Background Areas endemic of helminth infection, tuberculosis (TB) and HIV are to a large extent overlapping. The aim of this study was to assess the impact of asymptomatic helminth infection on the immunological response among TB patients with and without HIV, their house hold contacts and community controls. Methodology Consecutive smear positive TB patients (n = 112), their household contacts (n = 71) and community controls (n = 112) were recruited in Gondar town, Ethiopia. Stool microscopy, HIV serology, serum IgE level, eosinophil and CD4 counts were performed and tuberculosis patients were followed up for 3 months after initiation of anti-TB treatment. Results Helminth co-infection rate was 29% in TB patients and 21% in both community control and household contacts (p = 0.3) where Ascaris lumbricoides was the most prevalent parasite. In TB patients the seroprevalence of HIV was 47% (53/112). Eosinophilia and elevated IgE level were significantly associated with asymptomatic helminth infection. During TB treatment, the worm infection rate of HIV+/TB patients declined from 31% (10/32) at week 0 to 9% (3/32) at week 2 of TB treatment, whereas HIV-/TB patients showed no change from baseline to week 2, 29% (13/45) vs. 22.2% (10/45). This trend was stable at week 8 and 12 as well. Conclusion One third of smear positive TB patients were infected with helminths. Eosinophilia and elevated IgE level correlated with asymptomatic worm infection, indicating an effect on host immunity. The rate of worm infection declined during TB treatment in HIV+/TB co-infected patients whereas no decline was seen in HIV-/TB group.